Christianity 2019 What's Missing? A Call for Further Research - Zurlo, Gina A.; Johnson, Todd M. 1958-; Crossing, Peter F. (2019)
This article marks the thirty-fifth year of presenting statistical information on world Christianity and mission. This year, we report on three gaps in the literature, concerning women in world Christianity and mission, the status of short-term mission (STM), and missions and money. There are few quantitative studies on women in world Christianity; there remains a dearth in the literature on the magnitude and impact of STM (which is particularly US-centric); and Christian finance, now $60 trillion in personal income, is vastly under-researched in global studies.
Keywords: Christian finance; Demography; global studies; Mission; Money; short-term mission; Statistics; Women; World Christianity